FACTORS RELATED WITH THE COMPLIANCE OF FILLING THE MOTHER AND CHILD HEALTH (MCH) HANDBOOK IN POSTPARTUM CARE OF PRIVATELY PRACTICING MIDWIFE (PPM) - Tengku Dewi Agustina; Rully Rully (Journal of Midwifery, 2018)
In midwifery care standard,  midwives should carry out complete, accurate, brief and clear midwifery recording of the findings in providing midwifery care. Based on preliminary survey conducted on 5 PPM  , it was found that 100%  midwives did not fill the MCH handbook of postpartum care. This study aims to determine the factors related to compliance of MCH handbook by midwives in post partum care in PPM. This was descriptive analytic study with cross sectional design. . This study was conducted in September 2016 - July 2017.The population in this study is all PPM in Pekanbaru totalling 59 samples using purposive sampling. Data analysis was performed using Chi Square. The results showed that most midwives did not fill out the MCH handbook 81.4% .There was a significant relation between knowledge (p-value = 0,002) and motivation (p-value = 0,001) with compliance of MCH handbook by midwivese in postpartum care, there was no significant relation between duration of work (p-value = 0,468) in compliance of filling out MCH handbook. It is recommended for association of midwives to be more active in evaluation and monitoring through giving reward / punishment about filling out the MCH handbook